2012
DOI: 10.1097/md.0b013e31825f95b9
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant STAT3 Deficiency and Hyper-IgE Syndrome

Abstract: Autosomal dominant deficiency of signal transducer and activator of transcription 3 (STAT3) is the main genetic etiology of hyper-immunoglobulin (Ig) E syndrome. We documented the molecular, cellular, and clinical features of 60 patients with heterozygous STAT3 mutations from 47 kindreds followed in France. We identified 11 known and 13 new mutations of STAT3. Low levels of interleukin (IL)-6-dependent phosphorylation and nuclear translocation (or accumulation) of STAT3 were observed in Epstein-Barr virus-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
164
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(180 citation statements)
references
References 72 publications
(141 reference statements)
13
164
0
3
Order By: Relevance
“…On rare occasion, EBV lymphomas have been described in AD-HIES patients. However, in a recent cohort of 60 AD-HIES patients, 7% developed lymphomas, none associated with EBV (43). Whether deficiency of STAT3 in these patients may impact clinical outcomes of EBV infection also remains a question.…”
Section: Discussionmentioning
confidence: 99%
“…On rare occasion, EBV lymphomas have been described in AD-HIES patients. However, in a recent cohort of 60 AD-HIES patients, 7% developed lymphomas, none associated with EBV (43). Whether deficiency of STAT3 in these patients may impact clinical outcomes of EBV infection also remains a question.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the role of interleukin-17A (IL-17A) in clearance of pneumococcal carriage in mice (8,9). The increased incidence of pneumococcal sinopulmonary infections in patients with Job's disease (10), now understood to be due to a genetic defect in the STAT3 transcription factor which is essential for differentiation of IL-17-producing T H 17 cells (11), points to the importance of this effector cytokine in humans as a mechanism of protection against mucosal pneumococcal infections.…”
mentioning
confidence: 99%
“…HIES is due to defects in Janus activated kinase/signal transducer and activator of transcription (JAK-STAT)-mediated cytokine signals, including interleukin (IL)-6 and IL-23 [8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%